Perancangan Sistem E-Commerce Menggunakan OpenCart untuk Home Industry Makanan pada Usaha Mikro di Payakumbuh - Rival, Muhammad; Annas, Firdaus; Fattahul Safti Hasibuan, Asyahri (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This research aims to design an e-commerce system focused on the needs of micro-entrepreneurs, particularly in the food industry, to help MSMEs utilize digital technology to expand market reach in Payakumbuh. The system developed uses OpenCart as the main platform, designed to facilitate entrepreneurs in marketing their products through a web-based e-commerce platform. One of the main challenges in introducing products to the broader community is the reliance on traditional promotion methods, which limit market potential. In today's digital era, home industry products should already be competitive in the global market. However, many micro-entrepreneurs have yet to optimally leverage technology.The research adopts the Research and Development (R&D) method with the development stages of Planning, Production, and Evaluation (PPE). During the Planning stage, problems and needs of MSMEs were analyzed through surveys conducted on several food home industries in Payakumbuh. The Production stage involved designing an e-commerce application using the OpenCart platform as a medium to enhance sales. The Evaluation stage aimed to disseminate the research findings. The result of this study is a web-based promotional tool using the OpenCart application that can assist micro-entrepreneurs in introducing their products digitally. The findings indicate that OpenCart can be an effective solution to increase the competitiveness of home industry products in Payakumbuh, as well as make it easier for entrepreneurs to enter wider and global markets.